Linear and Nonlinear Thermal Lens Signal of the (Δν = 6) C–H Vibrational Overtone of Naphthalene in Liquid Solutions of n-Hexane. Issue 12 (December 2019) - Nyaupane, Parashu R.; Diaz, Marlon; Barton, Ann; Manzanares, Carlos E.
The thermal lens technique is applied to vibrational overtone spectroscopy of solutions of naphthalene (C10 H8 ) in liquid hexane. The C–H fifth vibrational (Δν = 6) overtone spectrum of C10 H8 is detected at room temperature for mole fractions from 0.08 to 19 × 10 −6 using n-C6 H14 as solvent. By detecting the absorption band in a 19 ppm (parts per million) solution, the peak absorption of the signal is approximately (2.2 ± 0.3) × 10 −7  cm −1 . A plot of normalized integrated intensity as a function of the mole fraction of naphthalene in solution reveals a dependence of the magnitude of the signal with the probe laser wavelength. If the wavelength of the probe laser is 568 nm, the thermal lens signal (TLS) is linear as a function of the mole fraction of the solution. When the wavelength of the probe laser is 488 nm, the TLS is nonlinear as a function of the concentration. Three different models of nonlinear absorption are discussed. A two-color absorption model that includes the simultaneous absorption of the pump and probe lasers could explain the enhanced magnitude and the nonlinear behavior of the TLS for solutions of mole fraction < 0.1%.